2021
DOI: 10.1155/2021/9774980
|View full text |Cite
|
Sign up to set email alerts
|

Acute Whole-Body Vibration Exercise Promotes Favorable Handgrip Neuromuscular Modifications in Rheumatoid Arthritis: A Cross-Over Randomized Clinical

Abstract: Objective. Rheumatoid arthritis (RA) causes progressive changes in the musculoskeletal system compromising neuromuscular control especially in the hands. Whole-body vibration (WBV) could be an alternative for the rehabilitation in this population. This study investigated the immediate effect of WBV while in the modified push-up position on neural ratio (NR) in a single session during handgrip strength (HS) in women with stable RA. Methods. Twenty-one women with RA (diagnosis of disease: ±8 years, erythrocyte s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…CA), adjusted to the second position [17]. Volunteers remained in a seated position, with the shoulder in adduction and 90° at the elbow joint, with the forearm in a neutral position [18][19][20]. Three measures of HS of the arm without arteriovenous fistula were performed and the average of these measures was used for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CA), adjusted to the second position [17]. Volunteers remained in a seated position, with the shoulder in adduction and 90° at the elbow joint, with the forearm in a neutral position [18][19][20]. Three measures of HS of the arm without arteriovenous fistula were performed and the average of these measures was used for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that a single bout of exercise may effectively decrease serum BDNF levels in patients with RA without, however, a possible explanation for this finding. Finally, Coelho-Oliveira AC et al [ 48 ] investigated the effect of acute whole-body vibration exercise under the hands, on handgrip strength, range of motion, and electromyography signals of women with RA, and demonstrated that it promotes neuromuscular modifications during the handgrip of women with stable RA. On the contrary, a recent systematic literature review that investigated the acute effects of exercise on pain symptoms, clinical inflammatory markers, and inflammatory cytokines in RA concluded that post-exercise responses for pain, clinical inflammatory markers and inflammatory cytokines were not different between people with or without RA [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WBV device is particularly helpful in individuals who are immobilized due to chronic health issues or have prolonged injuries, as typically seen in special needs, aging [22], overweight, and obese populations, as it is considered to be passive training, involving minimal risk of injury [23]. Prior research using WBV interventions have shown improvements in cardiovascular health [17,24], arthritis [25], flexibility [26], muscle soreness/stiffness [26], muscle strength/power [27], motor function and balance [28], and bone density [29] within mixed populations. However, to date, there is no published literature on the feasibility of WBV exercise training on autistic individuals or cardiovascular disease risk factors in sedentary and/or overweight individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%